Sistema alagoano de inovação : organização institucional necessária para o desenvolvimento - Albuquerque, Paula Pradines de (2012)
The economic growth of a region is related to the stock of attributes and local capacity to innovate, as result of interaction of different actors - companies, universities, government, financial institutions, among others - that have formal and non-formal relationships, shaping networks. In this context this paper performs the mapping about the development and technological capacity situational subject to contribution, legal framework to encourage innovation, considering institutional relationships and their performance, based on the model built by Etzkowitz - Triple Helix, as a way to analyze the regional development from the perspective of the Regional Innovation System. The intent to evaluate the current scenario and the possibilities of strengthening the Innovative and Productive System of the State of Alagoas, in order to provide elements for discussion of development and innovative policy in the state. For this purpose, we used the Delphi methodology, in which local experts are consulted in the matter under discussion, trying to get a consensus on the answers as a way to build a scenario or projection, especially in the absence of historical data. We consulted forty experts in different areas of knowledge and geographical reality of the state of Alagoas, in two rounds of questionnaires and interviews. How relevant results points to: a) the local productive sectors not follow the strategic guidelines of national policy, b) the state´s production, mostly, is intended for local demand, without the capacity to compete in other markets, reflecting of low maturity displayed; c) state of art of science development in the state, with low index of application in productive sectors, with few exceptions, d) state policies have been characterized as the most appropriate than federal policies; e) there is an imbalance in the current scenario of the Innovation System of Alagoas as their systemic relationships, which are often ad hoc and uncoordinated. The obtained results can be useful to mobilize all the forces of the state, establishing common goals, able to leverage local development.